STRATEGI DIVERSIFIKASI TERHADAP KINERJA PERUSAHAAN - Shinta Heru Satoto (Jurnal Keuangan dan Perbankan, 2009)
The purposes of this research were to provide an empirical evidence of the influenceof diversification to the firm performance. This research used 75 manufacturer firms thatdiversified their business. It also used control variable that describe firms characteristic, such asfirm size, debt ratio, current ratio, and firm age. The empirical result showed that thediversification strategy negatively influenced firm performance. It could be because the firmin Indonesia was under the conditions of unstable economics.